Duo-ethnography as the Qualitative Inquiry in Small Family Business Research - Sułkowski Łukasz; Marjański Andrzej (Management, 2018)
The research methodology of family businesses is increasingly becoming the subject of scientific discussion that shows how difficult and complex task it is. Research area is located on the border of several disciplines, which raises significant methodological problems.